Physiological responses to the special judo fitness test in elite Spanish judo athletes: a new monitoring approach - Casals, C.; Huertas, J. R.; Barranco-Ruiz, Y.; Escobar-Molina, R. (Revista de Artes Marciales Asiaticas, 2016)
The physiological assessment of the elite athlete is of critical importance for his/her health and competitive success. In judo, specific tests are required because the anaerobic capacity is responsible for the explosive scoring actions in combat, while the aerobic capacity is also essential for recovery during and between matches (Franchini, et al, 2013). In this regard, the Special Judo Fitness Test (SJFT) was developed by Sterkowicz (1995), and it is one of the most used tests in judo (Drid, et al, 2012), probably explained by its easy applicability and its specificity that makes the test more appropriate for the judoka evaluation than a Wingate test (Szmuchrowski, et al, 2013). However, the test only considers a few performance indicators; thus, the aim of our study was to assess additional physiologic markers during the SJFT execution in elite judo athletes.